2018
DOI: 10.4103/sja.sja_450_17
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal postcesarean section bupivacaine analgesia: Comparison between dexamethasone and dexmedetomidine as adjuvants

Abstract: Background:The peritoneal wound is frequently neglected during laparotomy. The preperitoneal local anesthetics and many adjuvants were effective for postcesarean analgesia. Analgesia may involve somatic and autonomic components. The preperitoneal bupivacaine and the promising adjuvants dexamethasone or dexmedetomidine were compared in this study.Patients and Methods:Sixty patients subjected to a cesarean section (CS) under general anesthesia divided into two groups using a bolus of preperitoneal bupivacaine 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The parietal peritoneum though pain sensitive was not anaesthetized and therefore postoperative pain control may be potentially suboptimal. 23 We did not include peritoneal spraying as the amount of BP absorbed from peritoneum is not well established. However, it has also been said that preperitoneal LA might not have added benefit over subcutaneous infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The parietal peritoneum though pain sensitive was not anaesthetized and therefore postoperative pain control may be potentially suboptimal. 23 We did not include peritoneal spraying as the amount of BP absorbed from peritoneum is not well established. However, it has also been said that preperitoneal LA might not have added benefit over subcutaneous infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The study in which dexmedetomidine and dexamethasone were compared in prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy (the patients received either single dose of dexmedetomidine or dexamethasone before skin incision) demonstrated that the patients in dexmedetomidine group had lower severity of pain, higher sedation score, requested the first analgesic postoperatively later, and the amount of postoperative administrated tramadol was lower (41). Similarly, in the study in which dexmedetomidine and dexamethasone were compared as adjuvants to bupivacaine analgesia in preperitoneal post-cesarean section lower pain scores, prolonged time to first analgesic request was observed in dexmedetomidine group (42).…”
Section: Impact Of Dexmedetomidine and Dexamethasone On Postoperative...mentioning
confidence: 91%
“…The proper tube position was confirmed by auscultation and fiberoptic bronchoscopy. The ventilation settings during surgery were tidal volume ( 7-10 mL kg -1 (ideal body weight) ), a fraction of inspired oxygen (0.5-1.0), and end-tidal CO 2 partial pressure (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Following surgery, patients were admitted to the Intensive Care Unit (ICU).…”
Section: Methodsmentioning
confidence: 99%